Deconstructing categories syncretic with the nominal complementizer. Issue 1 (5th March 2018) - Baunaz, Lena; Lander, Eric
Abstract : This paper investigates the internal structure of categories syncretic with the complementizer from a nanosyntactic perspective (cf. Starke 2009 ; 2014 ; Caha 2009 ). The (emotive factive) that- complementizer in Germanic, Romance, Hellenic, Slavic and Finno-Ugric languages has the same morphophonological form as other nominal categories, like demonstrative, interrogative, relative pronouns and indeterminate nouns. We claim that this homophony is not accidental. We also argue that these elements are internally complex and composed of syntactico-semantic features which are hierarchically ordered according to a functional sequence. More specifically, the internal structure can be considered essentially trimorphemic, being composed of (i) a lexical core or base which in our data is nominal (the nominal core called simply n ), (ii) an inflectional ending (which we label Infl or Φ), and (iii) a functional morpheme which resembles an article of sorts and often (but not always) appears as a prefix (which we label simply F). The n and Infl components in the structures studied here are invariant and can be shown to be quite small, while F, on the other hand, crucially varies in size, depending on the function of the relevant morpheme involved (Dem, Comp, Rel, Wh or Indet). Importantly languages may lexicalize each of these components ( n, Infl, and F) in different ways. Evidence for the fseq we are advocating comes from crosslinguistic patterns of syncretism and morphological containment.